Using the health action process approach to predict and improve health outcomes in individuals with type 2 diabetes mellitus - MacPhail M (Dove Medical Press, 2014)
Mariana MacPhail,1 Barbara Mullan,2 Louise Sharpe,1 Carolyn MacCann,1 Jemma Todd1 1School of Psychology, University of Sydney, Sydney, NSW, Australia; 2School of Psychology and Speech Pathology, Curtin University, Bentley, WA, Australia Background: The purpose of this study was to explore the predictive utility of the Health Action Process Approach (HAPA) and test a HAPA-based healthy eating intervention, in adults with type 2 diabetes mellitus. Materials and methods: The study employed a prospective, randomized, controlled trial design. The 4-month intervention consisted of self-guided HAPA-based workbooks in addition to two telephone calls to assist participants with the program implementation, and was compared to “treatment as usual”. Participants (n=87) completed health measures (diet, body mass index [BMI], waist circumference, blood pressure, blood glucose levels, lipid levels, and diabetes distress) and HAPA measures prior to the intervention and again upon completion 4 months later. Results: The overall HAPA model predicted BMI, although only risk awareness and recovery self-efficacy were significant independent contributors. Risk awareness, intentions, and self-efficacy were also independent predictors of health outcomes; however, the HAPA did not predict healthy eating. No significant time × condition interaction effects were found for diet or any HAPA outcome measures. Conclusion: Despite the success of HAPA in predicting health outcomes for those with type 2 diabetes mellitus, the intervention was unsuccessful in changing healthy eating or any of the other measured variables, and alternative low-cost health interventions for those with type 2 diabetes mellitus should be explored. Keywords: intervention, healthy eating, theory, risk awareness, self-efficacy